Evaluating the impact of game development-based learning on programming skill acquisition and student engagement - Nurul Hazlina Noordin; Gajendran Karunanithi (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study examines the challenge of limited engagement and conceptual understanding among school children in introductory programming education. To address this, the research evaluates the impact of game development-based learning using the slider game module. The objective is to assess how developing a simple game can support programming skill acquisition and enhance learner engagement. A total of 310 participants, aged 11 to 17, were selected through purposive sampling from various schools involved in programming classes. The research design included pre- and post-test assessments, demographic analysis, and Likert-scale surveys to gauge learner perceptions. Quantitative analysis was conducted using paired sample t-tests and descriptive statistics. The results show improvements in learners’ coding abilities and increased confidence and motivation across all age groups. The findings highlight the effectiveness of game development-based learning as a pedagogical approach for teaching programming in an engaging and impactful way.